Compound development as a protective layer on fecral substrate by a combination of γ-Al2O3 ultrasonic and NiO electroplating techniques to improve thermal stability - Imam Hidayat; Dafit Feriyanto; Supaat Zakaria; SS. Abdulmalik; Nurato Nurato; Dedik Romahadi (SINERGI, 2026)
One of the most technologically advanced methods for developing and adhering catalysts to the FeCrAl substrate is electrophoretic deposition. However, it faces a problem: low thermal stability at high temperatures of 10000 °C, caused by a lack of a protective oxide layer. The goal of this study is to investigate the protective oxide layers formed by Al2O3 and NiO coatings on FeCrAl metallic material for catalytic converters (CATCO). The electrolyte was prepared with distilled water at a constant temperature of 40±50 °C. The pH was adjusted to 5 with HCl and NaOH reagents. The electrolyte was prepared at 40 ± 50 °C and stirred for 1 minute using a magnetic stirrer. A 50mm x 10mm Ni plate substrate served as the anode, while a 40mm x 20mm FeCrAl cathode was used. The spacing between the anode and cathode was set at 25mm. The electroplating was conducted for several variation times of 15, 30, 45, 60 and 75 minutes, current density of 8 A/dm2, 3g γ-Al2O3 was inserted into the beaker for each sample and the total surface area was 1600mm2 on both sides. Drying was performed after electroplating at 600 °C for 12 hours.  Raman spectroscopy revealed that several compounds observed during the experimental stages, such as FeCrAl, γ-Al2O3, NiO, NaO2, NiAl2O4, NiCr2O4, and FeCr2O3, were also present in the coated FeCrAl CATCO, with distinct peaks. Therefore, it can be concluded that the UB+EL 30 min successfully deposited the γ-Al2O3 and NiO on the FeCrAl substrate after CATCO fabrication.